Employees' Perceptions of the Effects of Retrenchment on Job Stress and Organisational Commitment in a Mining Company - Seteni, Landiswa; Joubert, Pierre; Dhurup, Manilall (African Journal of Employee Relations, 2019)
Over the past decade, South African organisations have had to cope with an ever-increasing rate of local and global changes. There have been considerable and ongoing socio-political changes, resulting from new government regulations. Most organisations have experienced some type of downturn, whether due to external business factors or poor internal performance. A typical response to organisational decline is retrenchment. Our study sought to explore employees’ perceptions of the effects of retrenchment on job stress and organisational commitment in a mining company. The study was located within a quantitative research paradigm. Four research hypotheses were posited and data was collected in one region from a sample of 400 surface mining employees, including management, administrators, engineers and artisans. The results showed that the effects of retrenchment did not have a negative impact on job stress (time stress and anxiety). This may be due to the fact that the mining company in question had a planning and consultation process in place for the employees prior to the retrenchment process. The results also showed that job stress (time stress and anxiety) was negatively associated with organisational commitment. To conclude this article we discuss the implications of our findings, outline the limitations of our study and make recommendations for future research.